The Influence of Financial Literacy and Love of Money on the Financial Performance of MSMEs in Denpasar City - I Nyoman Hendra Aryadi; Ni Made Puspa Pawitri; Ni Ketut Nadila Suryasari; Made Yessi Puspitha (CV Edujavare Publishing, 2026)
This study aims to analyze in-depth the influence of Financial Literacy and Love of Money on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Denpasar City, both partially and simultaneously. The research method used is associative quantitative research. The population in this study included all MSMEs in Denpasar City, with a final sample of 100 respondents selected selectively using purposive sampling based on the criteria of NIB ownership and internal bookkeeping. Data collection used a structured questionnaire with a 5-point Likert scale, which was then processed using IBM SPSS Statistics 30. Data analysis methods used included multiple linear regression analysis, comprehensive classical assumption testing, and hypothesis testing (partial t-test and simultaneous F-test). The results of the partial study indicate that Financial Literacy has a positive and significant effect on MSME financial performance (beta = 0.926, p < 0.001). Furthermore, the Love of Money variable was also shown to have a positive and significant effect on the financial performance of MSMEs (beta = 0.609, p < 0.001). Simultaneously, testing showed that Financial Literacy and Love of Money had a positive and significant effect on the financial performance of MSMEs in Denpasar City with a significance value of p = 0.001. The empirical findings of this study support the integration of Resource-Based View (RBV) and Attribution Theory, which emphasizes that cognitive capacity in the form of financial understanding (Financial Literacy) and internal psychological drive directed toward money (Love of Money) are a combination of strategic non-physical assets that are essential in driving optimal business financial performance.